2006
DOI: 10.1016/j.brainres.2006.09.096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time pressure on verbal self-monitoring: An ERP study

Abstract: The Error-Related Negativity (ERN) is a component of the event-related brain potential (ERP) that is associated with action monitoring and error detection. The present study addressed the question whether or not an ERN occurs after verbal error detection, e.g., during phoneme monitoring. We obtained an ERN following verbal errors which showed a typical decrease in amplitude under severe time pressure. This result demonstrates that the functioning of the verbal self-monitoring system is comparable to other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 38 publications
(69 reference statements)
7
70
2
Order By: Relevance
“…Only a small number of studies have specifically investigated verbal self-monitoring using functional imaging. These studies have used either EEG/MEG (Ganushchak & Schiller, 2006Maess et al, 2002) to investigate the time course and/or signal amplitude associated with verbal self-monitoring, or fMRI and PET through the use of distorted, masked, or delayed verbal feedback (Christoffels, Formisano, & Schiller, 2007;Fu et al, 2006;Hashimoto & Sakai, 2003;McGuire et al, 1996). Several EEG and MEG studies have pointed to a role for the left temporal cortex in self-monitoring, however, they cannot provide specificity in terms of anatomical regions.…”
Section: Self-monitoring In Speech Production and The Source Of The Cmentioning
confidence: 99%
“…Only a small number of studies have specifically investigated verbal self-monitoring using functional imaging. These studies have used either EEG/MEG (Ganushchak & Schiller, 2006Maess et al, 2002) to investigate the time course and/or signal amplitude associated with verbal self-monitoring, or fMRI and PET through the use of distorted, masked, or delayed verbal feedback (Christoffels, Formisano, & Schiller, 2007;Fu et al, 2006;Hashimoto & Sakai, 2003;McGuire et al, 1996). Several EEG and MEG studies have pointed to a role for the left temporal cortex in self-monitoring, however, they cannot provide specificity in terms of anatomical regions.…”
Section: Self-monitoring In Speech Production and The Source Of The Cmentioning
confidence: 99%
“…However, these authors do not make an explicit link between the negativity they found in their study and the ERN. Ganushchak and Schiller (2006) used a phoneme-monitoring task to investigate the effects of verbal monitoring under time pressure. Participants were presented with pictures and had to indicate whether the target phoneme was present in the name of the picture.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that an ERN can be elicited by verbal errors (e.g., Ganushchak & Schiller, 2006;Sebastián-Gallés, Rodríguez-Fornells, De Diego-Balaquer, & Díaz, 2006;Masaki, Tanaka, Takasawa, & Yamazaki, 2001). For instance, Masaki et al (2001) examined whether the ERN occurs in relation to speech errors in the Stroop color-word task.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these authors concluded that ERN-like components can also be found after vocal slips. Ganushchak and Schiller (2006) used a phoneme monitoring task to address the question whether an ERN occurs after verbal error detection and whether a potential ERN is affected by a time pressure manipulation. These authors obtained an ERN following verbal errors.…”
Section: Introductionmentioning
confidence: 99%